Важка доля героя Другої світової війни з Чернігівщини: Андрій Федотович Савенко (1912 – 1988) - Шумило, С.В.; Шумило, В.В. (Сiверянський літопис, 2021)
Мета статті – розкрити віхи біографії нашого співвітчизника Савенка Андрія Федотовича (1912–1988). Використані методи: біографічний, історичного об’єктивізму. Новизна статті полягає у висвітленні життєвого шляху простої людини, крізь призму якого розглянуто ключові моменти історії нашої батьківщини XX ст.: розкуркулення, розкозачення, концтабори, утеча від переслідувань, Друга світова війна. Актуальними є судження свідка та учасника тих трагічних подій про сенс цього періоду історії для життя людини. Неординарними є такі вчинки А. Ф. Савенка, як знищення партбілету та переосмислення ключових життєвих подій. У заключній частині статті запропоновано короткій огляд того, як склалася доля нащадків А. Ф. Савенка. The Aim of the article: To describe the most important episodes of the biography of one of our countrymen: Savenko Andrei Fedotovich (1912–1988). Methods used: Biographical and historical objectivism. The new approach used in this article is the use of the biography of an ordinary person. Through the prism of his life we can describe and better understand the key events in the history of our homeland in the XX century: dekulakization, the destruction of the Cossacks, concentration camps, escaping persecution, World War II. The judgement and discourse of a witness and participant of the tragic events of that period of our history about their meaning and the role they played in individual lives is especially significant. Especially important are such episodes in the life of A.F. Savenko as the destruction of his communist party membership card and his reevaluation of the key events of his life. The concluding part of the article includes a short account of the fates of A. F. Savenko’s descendants.